Amine-functionalized SiO2 nanodot-coated layered double hydroxide nanocomposites for enhanced gene delivery - Li, L.; Gu, W.; Liu, Jian; Yan, S.; Xu, Z. (Tsinghua University Press, 2015)
In this work a novel strategy has been developed to prepare well-dispersed amine-functionalized SiO2 nanodot-coated layered double hydroxide nanocomposite (NH2-SiO2@LDH) via electrostatic interactions and condensation of (3-aminopropyl)triethoxysilane (APTES). This nanocomposite system is well dispersed in culture media and phosphate buffered saline, and exhibits low cytotoxicity and good biocompatibility. The fluorescence microscopy images and flow cytometry data indicate that such an NH2-SiO2@LDH nanocomposite is able to efficiently deliver small interfering RNA (siRNA) into the U2OS cell line to inhibit cell proliferation. Thus, NH2-SiO2@LDH nanocomposite has a great potential as a nanocarrier for efficient gene delivery.